Pedagogical Approaches that Facilitate Writing in Postgraduate Research Candidature in Science and Technology - Catterall, Janice; Ross, Pauline; Aitchison, Claire; Bergin, Shelley (Journal of university teaching & learning practice, 2011)
The current higher education climate seems to be demanding increasing levels of written output from doctoral researchers during candidature. In this context this study employed an online questionnaire, individual interviews and focus group discussions to collect information on the challenges and successes of doctoral writing. It was found that feedback on student writing was universally regarded as the primary pedagogical tool for teaching and learning research writing and for most, the supervisor's role was central to this. Some supervisors employed "writing for publication" as a complimentary tool. A number of supervisors and students also reported positively about the value of participating in social writing and critiquing environments such as writing groups, writing retreats, or writing for peer feedback. This research suggests that there would be benefit in tertiary institutions pursuing a more systematic approach to the support of writing both as a learning tool for research students and for the promotion of a vibrant, scholarly, research community.